Microglandular adenosis associated with triple-negative invasive breast carcinoma – a case report and literature review - Zielinska, Aleksandra; Matczak, Mateusz; Stachura, Laura; Kubiak, Robert; Michalski, Tomasz; Romańska, Hanna; Braun, Marcin (Contemporary Oncology/Współczesna Onkologia, 2025)
Microglandular adenosis (MGA) is a rare benign breast condition characterized by disorganized small glands composed of epithelial cells without myoepithelial components. Microglandular adenosis can coexist with invasive breast cancer (IBC), particularly the triple-negative (TN) subtype. Emerging evidence suggests MGA may be a precursor to IBC, supported by shared morphological and molecular features. We present the case of a 66-year-old woman with a palpable mass in the left breast. Initial mammography and biopsy suggested malignancy. The patient underwent breast-conserving surgery with resection of the sentinel lymph node. Histopathological analysis confirmed triple-negative, basal-like invasive breast carcinoma with focal salivary gland-type carcinoma differentiation, likely arising from an MGA-like component. The patient subsequently received adjuvant chemotherapy, and no recurrence was observed after a 30-month follow-up. This case underscores the importance of recognizing MGA as a potential precursor to invasive breast carcinoma, particularly the TN subtype. Increased awareness and the use of comprehensive diagnostic methods are essential for improving patient outcomes and managing the risks associated with MGA, especially in cases that may progress to more aggressive forms of cancer.